KOMUNIKASI KELOMPOK TERARAH (FGD ) TENTANG ANEMIA PADA REMAJA DI DESA LAMPINEUNG KECAMATAN BAITUSSALAM KABUPATEN ACEH BESAR - Raudhatun Nuzul ZA; Ade Dita Puteri; Rulia Meilina (Universitas Pahlawan Tuanku Tambusai, 2022)
Anemia is one of the nutritional problems in adolescent girls. Anemia is a condition when the hemoglobin level in the blood is less than the normal value (<12gr/dl) in women which is characterized by clinical symptoms, namely lethargy, weakness, dizziness, light-headed eyes, and pale face. This activity was carried out using the FGD (Focused Group Communication) method in order to provide a detailed understanding to adolescents about responding to problems regarding anemia from an early age and in order to improve health status by consuming blood booster tablets, iron, and preventing anemia. The FGD method is effective because it has an informal and relaxed atmosphere so that the participants are more flexible and open in expressing their respective opinions. adolescence. The method of implementing this activity uses online and offline methods provided by the resource person or the extension agent. The results of this activity the youth understand and provide good feedback from the information submitted. The conclusion of this activity is that adolescents are able to understand and understand the meaning of anemia and can understand how to respond to the occurrence of anemia. Keywords: FGD, Anemia, Adolenscens